An Approach to Angélica Liddell's Theatrical Poetics (XXI Century. Spanish Literature and Culture, 2019)
Angélica Liddell (Figueras, 1960) is one of the most outstanding voices in the contemporary theater scene. His theatrical production focuses on pain and is, fundamentally, the result of a personal search for human truth and its darker and more veiled aspects. The "Theater of the Passion" is closely linked to the importance of the actor's stage presence as "body of the text." It is a meta-reflexive discourse, apparently own and spontaneous, characterized by subversion, expressive force, direct interpellation to the viewer and for offering a broad horizon of meaning.
Keywords: Theater Studies; Postdramatic Theatre; Theatrical Poetics; Angélica Liddell; Poetic Theatricality